Studies on the factors shaping the Polish and Belarus transborder cooperation - Maria Ciechocinska (European Regional Science Association (ERSA), 2001)
The paper discusses the numerous sources of the difficulties encountered in the functioning of Poland's eastern border and analysis their diverse nature. It has been pointed out that they are generated to large extent by geopolitical factors, which hold the key to their successful solution. The paper concerns in a role of mentality and demons of past in shaping geopolitical premises. Due to the absence of sufficiently developed endogenous factors in the region the early years of the process of transformations proved that the incentives for growth can come from the asymmetry of economic potentials that exists between the regions of Poland and the border regions of the former Soviet republics. In this way, thanks to exegenous factors, the potentials on both sides of the border get balanced, a phenomenon known from earlier studies. It can be expected that in future the region will generate its own growth factors through complementary cooperation. From the point of view of the functioning of the future external border of the EU, the paper deals with two problems. The first deals with the shortfalls in transport infrastructure and the widely known problems with the functioning of trans-European transport corridors, where the border crossings remain the crucial spots. The second problem concerns the operation of the private sector or indeed of the presence of an environment for private enterprise, which is also taken up in the context of geopolitical factors, due to the impact it can have on the introduction of constructive changes leading to the establishment of durable goodneighbourly relations. History shows that this can be a highly effective tool for uprooting old prejudice as it permits the relatively fast emergence of new economic ties stemming from shared interests and it is generally conductive to opennes. This view was borne out by empirical studies into the functioning of Polands's eastern border. Only if the conditions for the development of local and regional enterpreneurship in border regions are guaranteed, can the European challenges to the functioning of eastern border bear fruit.
Keywords: 330